Lyman Abbott letter - Abbott, Lyman, 1835-1922.
TLS (New York, N.Y.; 1877 January 2) written by Abbott, as editor of The Christian Union, to Hubert P. Main, a Christian composer, requesting his help in writing a tribute to fellow religious composer Philip P. Bliss.
Editor.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bliss, Philip -- 1787-1857.; Main, Hubert P. -- 1839-1925 -- Correspondence; Christian union; Composers. -- United States; Editors